2017
DOI: 10.1080/14767058.2017.1322949
|View full text |Cite
|
Sign up to set email alerts
|

Poorer maternal diet quality and increased birth weight*

Abstract: Poorer third trimester maternal diet quality was associated with higher birth weight and longer length, but was unrelated to markers of infant adiposity. GWG was independent of third trimester maternal diet composition and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
(34 reference statements)
1
42
3
1
Order By: Relevance
“…The characteristics of observational studies are presented in Supplemental Table 3 . They were published from 1995 to 2018 and the majority were prospective cohorts ( n = 32) (14–27, 29, 31, 36–47, 49, 51), with the rest having case–control (35), cross-sectional (50), retrospective (28, 48), and mixed retrospective and prospective cohort design (30). Sample sizes ranged from 35 to 72,072, with participants of mean age 21–33 y and prepregnancy BMI 20–30 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of observational studies are presented in Supplemental Table 3 . They were published from 1995 to 2018 and the majority were prospective cohorts ( n = 32) (14–27, 29, 31, 36–47, 49, 51), with the rest having case–control (35), cross-sectional (50), retrospective (28, 48), and mixed retrospective and prospective cohort design (30). Sample sizes ranged from 35 to 72,072, with participants of mean age 21–33 y and prepregnancy BMI 20–30 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis reported that a diet rich in fruits, vegetables, whole grains, and fish combined with lower intakes of red and/or processed meats and high-fat dairy products was associated with a lower risk of gestational diabetes [14]. Moreover, poorer diet quality during pregnancy has been associated with birthweight and neonatal adiposity [13,15]. However, in these studies, diet quality was not assessed at each trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In a small pilot study (n = 41) assessing dietary quality and fetal growth using the Healthy Eating Index (HEI‐2010), which is formulated based on the 2010 Dietary Guidelines for Americans, a 10‐point lower HEI‐2010 score was associated with 200 g higher infant birthweight . In contrast, an American study (n = 893) found that when dietary quality was assessed in the third trimester using the Alternative Healthy Eating Index for Pregnancy and the Alternate Mediterranean Diet, there was no relation with neonatal outcomes at birth, including birthweight and SGA …”
Section: Discussionmentioning
confidence: 99%